Social support for veterans taking part in military service outside their country’s borders - Paulina Mendrek; Beata Osiak; Krzysztof Goniewicz (Health Psychology Report, 2019)
Soldiers who return to their country of residence after military service are subject to numerous, mostly negative, effects linked to exposure to stress. Post-traumatic stress disorder is one of the most common anxiety disor-ders, one which develops as a result of being exposed to traumatic experiences, both psychological and physi-cal. Post-traumatic stress disorder is also the main result of participation in active armed combat impacting war veterans, concerning mostly service undertaken outside their home country. Consequently, proper psychologi-cal preparation for armed combat, psychological support during service, as well as the support granted after soldiers return home, are of critical importance. This work characterises social support which is given to army personnel involved in armed combat. Methods of social involvement, which are provided to the soldiers taking part in military service outside their country, have also been described. The paper itself was written for two rea-sons: firstly, in order to exchange knowledge mainly in the areas of psychology and sociology; and secondly, to focus attention on those soldiers struggling with issues resulting from participation in military service outside their home country.